1996
DOI: 10.1016/s0022-5347(01)66241-4
|View full text |Cite
|
Sign up to set email alerts
|

Minimally Invasive Therapies in the Treatment of Erectile Dysfunction in Anticoagulated Cases: A Study of Satisfaction and Safety

Abstract: The adverse effects of vacuum therapy and intracavernous self-injection in patients on warfarin do not exceed the rate in the general urological population. These therapies appear to be safe in patients receiving warfarin.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
11
0
2

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(14 citation statements)
references
References 14 publications
1
11
0
2
Order By: Relevance
“…This study provides information on the risks and benefits in such a situation. Of note, our data are consistent with studies suggesting the safety of intramuscular (6) and other (7) injections in such patients.…”
Section: Discussionsupporting
confidence: 91%
“…This study provides information on the risks and benefits in such a situation. Of note, our data are consistent with studies suggesting the safety of intramuscular (6) and other (7) injections in such patients.…”
Section: Discussionsupporting
confidence: 91%
“…30 Patients with bleeding disorders or those on anticoagulation therapy are considered at high risk to develop petechiae, eechymosis or hematoma; 7 however, it was shown that the risk did not exceed that of the general population. 31 …”
Section: Contraindicationsmentioning
confidence: 99%
“…63 In only 11 (1.6%) of 706 documented vacuum applications and three (0.5%) of 605 self-injections, ecchymoses of the penile skin were recorded in patient diaries, indicating that the risk of bleeding, both in vacuum therapy and self-injection therapy, is not higher in the group receiving anticoagulants than it would be in a normal patient population. In the author's clinical practice, following 10 patients treated with the anticoagulant marcoumar for a number of years, no severe bleeding complications have been observed.…”
Section: Calcitonin Gene Related Peptide Combined With Pgementioning
confidence: 96%